Air Quality Information Based on Iot for Mobile Environment - Suresh Kumar, M.; Balaji, S. (International Journal of Engineering and Technology, 2018)
This paper describes about our proposed system in which it is able to monitor the quality of the air which is sufficient for the personâ€™s survival. In this, the level of carbon-mono-oxide that is the CO level in the environment is also checked.It is useful for monitoring and verifying the leakage of any poisonous air in the environment.The systemÂ can be designed to work based on the web application or the android application.The gas detector has been developed using the micro controller in order to measure the values of CO in them.For the purpose of getting information about the temperature that prevails in the environment the temperature sensors are used. In this proposed system the user can get warning about the level of the poisonous gas inÂ the environment by means of an alert message to the person or by get the location of the incident by means of the GPS. The proposed system produces the result by means of creating the graph values for the safe level of CO in the air.The threshold values can also be included in order to plot the graph.